ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA POKOK BAHASAN KOMPOSISI FUNGSI DI SMK BAKTI PURWOKERTO - Arum Setya Utami (AlphaMath : Journal of Mathematics Education, 2017)
This research aims to know the errors of students in solving the question of the story thesubject of composition of functions. This research is a descriptive qualitative researchqualifies. The subject of this research is the grade XI SMK Bakti Purwokerto. Based on theresults of the analysis of the answers to questions given to students, other forms of errorscommitted students is an error stating the problem, determine what the error was asked from aproblem, understand the error information of a problem, and not careful in counting.Keyword: error analysis, a matter story, composition of functions